Classification of Metacognitive into Two Catagories to Support the Learning Process - Husnul Rahmawati Sakinnah; Adhistya Erna Permanasari; Indah Soesanti (Jurnal Pendidikan Sains, 2017)
Abstract: Learning outcomes are the patterns of actions, values, understanding, attitudes, appreciation and skills. Learning outcomes are related to the metacognitive of student where the elements contained in metacognitive is cognitive. The relationship between cognitive and metacognitive which is the foundation of cognitive is metacognitive. There are two components such as knowledge of metacognitive and regulation of metacognitive. In the learning process, cognitive factors are not the only one that can support, but also a metacognitive factor is a very influential factor for the success of the learning process. Thus, it is very important to do with a deeper analysis about metacognitive by identifying me-tacognitive level to support the learning process. Identification of metacognitive is performed by using Naïve Bayes Classifier algorithm (NBC) which NBC is one of an algorithm that is used for classification algorithm for data mining. In these studies, it is obtained that the accuracy scored 88,0597% when tested using NBC. Key Words: metacognitive, knowledge of metacognitive, regulation of metacognitive, cognitive, Naïve Bayes Classifier (NBC)